2018
DOI: 10.1111/cea.13084
|View full text |Cite
|
Sign up to set email alerts
|

The use of omalizumab in allergen immunotherapy

Abstract: Although omalizumab (anti-IgE) is currently only approved for the treatment of asthma and chronic idiopathic urticaria, it has also been studied as an off-label treatment for numerous allergic conditions, including use as an adjunct to allergen immunotherapy in the treatment of allergic rhinitis, asthma, venom hypersensitivity and food allergy. We conducted a review of publications involving the use of omalizumab with allergen immunotherapy, by searching PubMed with key search terms of "omalizumab" and "immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 71 publications
(233 reference statements)
0
57
0
3
Order By: Relevance
“…Omalizumab treatment with allergen immunotherapy helps to potentiate increases in Treg activity by reversing the Th2 cell-like program (156). Using allergen OIT with anti-IgE antibodies in clinical studies showed promise, although not in all studies (157)(158)(159)(160). Anti-IL-5 antibodies (mepolizumab, reslizumab) have been FDA-approved for treating eosinophilic asthma (161), and several clinical trials support their effectiveness for EoE, although while esophageal eosinophilia improved, clinical symptoms were only modestly improved compared with typical improvements seen with topical glucocorticoids or dietary elimination therapy (162)(163)(164).…”
Section: Future Directionsmentioning
confidence: 99%
“…Omalizumab treatment with allergen immunotherapy helps to potentiate increases in Treg activity by reversing the Th2 cell-like program (156). Using allergen OIT with anti-IgE antibodies in clinical studies showed promise, although not in all studies (157)(158)(159)(160). Anti-IL-5 antibodies (mepolizumab, reslizumab) have been FDA-approved for treating eosinophilic asthma (161), and several clinical trials support their effectiveness for EoE, although while esophageal eosinophilia improved, clinical symptoms were only modestly improved compared with typical improvements seen with topical glucocorticoids or dietary elimination therapy (162)(163)(164).…”
Section: Future Directionsmentioning
confidence: 99%
“…Premedication with omalizumab in patients with recurrent intolerance reactions under venom immunotherapy improved tolerance in many cases [30][31][32][33][34][35]. However, uncertainty remains regarding the necessary duration and dose of omalizumab.…”
Section: Combining Scit With Biologic Agents (Anti-ige: Omalizumab)mentioning
confidence: 99%
“…More recently, it has been authorized for the use in patients with chronic spontaneous urticaria [27]. Additionally, off-label use of Omalizumab has revealed its efficacy in facilitating allergen updosing and desensitization in allergen-specific immunotherapy [28,29]. Omalizumab binds IgE with high affinity (K D~ 7 x 10 -9 M) [30].…”
Section: Classical Inhibition Of Free Serum Igementioning
confidence: 99%